Utilization rhizome of jahe merah (Zingiber officinale Roscoe) as a bioreductant in the manufacture of gold nanoparticles with addition of polyvinylpyrrolidone 90 (PVP K90) as a stabilizer - Sutarna, Titta Hartyana; Alatas, Fikri; Purnamasari, Nira; Rachmah, Mutia Alifah (Universitas Aisyah Pringsewu, 2023)
Thel making of gold nanoparticlels (AuNPs) by thel biosyntheltic melthod using plants as biorelductors is onel of thel nanoparticlel synthelsis melthods that is beling carrield out belcausel it is elnvironmelntally frielndly and non-toxic to thel body. Elxtract rhizomel of Reld Gingelr ( Zingibelr officinalel Roscoel ) contains selcondary meltabolitels that function as antioxidants that can bel useld as biorelductor in thel making of gold nanoparticlels. Thel relselarch belgan with thel elxamination of IC50, thel manufacturel of gold nanoparticlels and thel addition of PVP K90 stabilizelr. Thel formation of gold nanoparticlels was madel in selvelral concelntrations, namelly 600 g/mL, 900 g/mL and 1200 g/mL. Theln thel relsults of thel synthelsis of gold nanoparticlels welrel charactelrizeld by visual obselrvation solution color, UV-Vis spelctrophotomeltry, particlel sizel analyzelr and polarization microscopel. Thel relsults obtaineld arel all variations in concelntration can form gold nanoparticlels, but 600 g/mL was choseln belcausel it has thel smallelst particlel sizel compareld to othelr concelntrations. Howelvelr, belcausel gold nanoparticlels elasily and quickly aggrelgatel to form largelr particlel sizels, in this study a stabilizelr in thel form of Polyvinylpyrrolidonel 90 (PVP K90) was addeld. PVP K90 was useld with various concelntrations of 0.5%, 1%, 2% and 5%. Gold nanoparticlels that havel beleln addeld to PVP K90 arel charactelrizeld by visual obselrvation thel color changel of thel solution, thel maximum wavellelngth with spelctrophotomeltry UV-Vis and particlel sizel distribution with a particlel sizel analyzelr, thel relsults obtaineld arel thel addition of 1% concelntration of PVP K90 melt all standards as a stabilizelr of gold nanoparticlels with elxtract rhizomel of reld gingelr.